Home Visiting Utilization among a Sample of Teen Mothers: The Full Story. - Herrick, Katrine. (2017)
Abstract: Child maltreatment can have severe developmental impacts. Home visiting programs aim to prevent child maltreatment, but a review of several evaluations demonstrates inconsistent results regarding child maltreatment prevention. One approach to understanding this variation is to investigate outcome-dosage (amount of service) relationships through process evaluations. In a number of evaluations, dosage primarily refers to the home visit; however, the second Massachusetts Healthy Families Evaluation (MHFE-2), of which this thesis is a part, has expanded the definition of utilization to include non-home visit, or secondary, activities. This thesis is MHFE-2's pilot study exploring secondary activity utilization. Findings indicate that while age, education and employment status are largely unrelated to secondary activity utilization, community context, defined in this thesis by percent minority, poverty level, and density, does plays a role in secondary activity utilization. This understanding can contribute to further MHFE-2 utilization studies.; Thesis (M.A.)--Tufts University, 2011.; Submitted to the Dept. of Child Development.; Advisor: Francine Jacobs.; Committee: Barbara Parmenter, and Sarita Rogers.; Keywords: Individual & Family Studies, and Social Research.